2013
DOI: 10.1371/journal.pone.0054529
|View full text |Cite
|
Sign up to set email alerts
|

Fungi in Thailand: A Case Study of the Efficacy of an ITS Barcode for Automatically Identifying Species within the Annulohypoxylon and Hypoxylon Genera

Abstract: Thailand, a part of the Indo-Burma biodiversity hotspot, has many endemic animals and plants. Some of its fungal species are difficult to recognize and separate, complicating assessments of biodiversity. We assessed species diversity within the fungal genera Annulohypoxylon and Hypoxylon, which produce biologically active and potentially therapeutic compounds, by applying classical taxonomic methods to 552 teleomorphs collected from across Thailand. Using probability of correct identification (PCI), we also as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…This clade is clearly resolved from other genera, Nemania, Xylaria, and Biscogniauxia, by both maximum likelihood and Bayesian phylogenetic approaches. The genera containing cineole producers are closely related, and although their phylogenetic relationship was not resolved by ITS sequencing alone in our tree, consistent with previous publications, we can observe to which of these groups our isolates are most closely related (49).…”
Section: Voc Analysis Of Fungalsupporting
confidence: 91%
See 1 more Smart Citation
“…This clade is clearly resolved from other genera, Nemania, Xylaria, and Biscogniauxia, by both maximum likelihood and Bayesian phylogenetic approaches. The genera containing cineole producers are closely related, and although their phylogenetic relationship was not resolved by ITS sequencing alone in our tree, consistent with previous publications, we can observe to which of these groups our isolates are most closely related (49).…”
Section: Voc Analysis Of Fungalsupporting
confidence: 91%
“…The primers used for amplification were ITS1 (TCCGTAGGTGAACCTGCGG) and ITS4 (TCCTCCGCT-TATTGATATGC), and the resulting PCR products were sequenced by the W. M. Keck Foundation (48). A phylogenetic tree was constructed comparing the ITS sequence of cineoleproducing isolates from this study with previous cineole producers (CI-4, Ni25-2A, and EC12) and taxa reported in several recent molecular phylogenetic studies of genera in the family Xylariaceae (Table 1) (49,50). Sequences were aligned using MUSCLE version 3.8.31, and the phylogenetic tree was constructed using Bayesian (MrBayes version 3.2.0) and maximum likelihood methods (RAxML version 7.2.8) (51,52).…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenetic trees were rooted with two sequences under Gloeocantharellus persicinus and Gloeocantharellus purpurascens. Gaps were treated as missing data [13]. Branch lengths equal to zero were collapsed to polytomies.…”
Section: Supplementary Parsimony and Bayesian Analysesmentioning
confidence: 99%
“…Probability of Correct Identification (PCI) was calculated according Suwannasai et al . (), using the previous aligments. The p‐Distance (also known as ‘uncorrected distance’, the fraction of aligned nucleotide pairs that are not identical pairs) was used to calculate the PCI values.…”
Section: Methodsmentioning
confidence: 99%